Faktor-faktor yang berpengaruh terhadap Minimum Acceptable Diet pada anak usia 6-23 bulan di Indonesia - Muh. Guntur Sunarjono Putra; Mira Dewi; Lilik Kustiyah; Trias Mahmudiono; Cindra Tri Yuniar; Siti Helmyati (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2022)
Indonesia is one of the countries with high nutritional problems caused by inadequate feeding practices. A minimum acceptable diet (MAD) is used to assess feeding practices in children with low achievement (53,6%) aged 6-23 months. This study aimed to determine the factors influencing MAD in children aged 6-23 months in Indonesia. This study uses a cross-sectional study design to use secondary data from the 2017 IDHS. The subjects in this study were 4.783 children aged 6-23 months. Data were collected using the 2017 IDHS and WHO UNICEF 2010 questionnaires in assessing feeding practices. Statistical tests used were Chi-square, Spearman, and Multiple logistic regression. This study showed that the prevalence of MAD was 53.7%. Factors influencing MAD were the location of residence (p= 0,001), wealth index (p<0,001), mother's occupation (p= 0,007), father's education level (p= 0,022), mother's education (p= 0,003), media exposure (p= 0,012), geographic area (p<0,05), child's age (p<0,001), and birth order (p<0,05). The dominant factor influencing MAD is the education level of mothers who do not attend school. In conclusion, there is an influence between socio-demographic and economic characteristics and the characteristics of children with MAD in Indonesia.